THE STUDY OF DRYING RATE AND PHYSICAL CHARACTERISTICS OF DRIED NOODLES WITH MIXED TAPIOCA AND WHEAT FLOUR - kurniasari, eliya (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
The purposes of this researchwere to knowthe effect of adding strach flour as a substitution material of wheatflour on the drying rate, physical characteristics and to compare the physical characteristics of dried noodleswith commercial noodles. The experimentwas designedwith four different composition ratio of starch flour andwheat flourwich are 0 : 100%; 10 : 90%; 20 : 80%, and 30 : 70% and simboleized with C0, C10, C20, and C30. Theresults of the coefisient of drying rate (k) of C0 is 0,014, higher than the other compositions. Furthermore , theadding of starch flour tends to decrease the cooking loss, water absorption and unfurl ratio, but tends to increasethe water content and the tensile strength of the noodles. Comparison between dried noodles and commercialnoodles on the physical characteristics did not significant different. The dried noodles showed the similarphysical characteristics to the commercial noodles.Keywords :dried noodles , the rate of drying ,wheat flour, tapioca flourand physical characteristics